Pengaruh Ukuran Perusahaan dan Kinerja Lingkungan Terhadap Penerapan Akuntansi Manajemen Lingkungan (Studi Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023): Studi Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Aliya Fadilah; Ranti Pujie Lestari; Novie Susanti Suseno (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of company size and environmental performance on implementing environmental management accounting (EMA) in mining companies listed on the Indonesia Stock Exchange (IDX) for 2019-2023. This research adopts a descriptive-verificative method with a quantitative approach, utilizing secondary data such as financial reports, sustainability reports, and PROPER ratings. The findings indicate that company size significantly affects the implementation of EMA, where larger companies are more capable of adopting EMA practices due to their greater resources. Environmental performance also significantly impacts EMA implementation, as companies with higher PROPER ratings tend to be more transparent and proactive in managing environmental impacts. Simultaneously, both variables contribute significantly to the adoption of EMA. The implications of this study highlight the critical role of EMA in supporting corporate sustainability through better environmental management.